UML FOR JAVA™ PROGRAMMERS - Martin, Robert (Robert C. Martin series., 2003)
UML for Java Programmers Robert C. Martin All the UML Java developers need to know You don't use UML in a vacuum: you use it to build software with a specific programming language. If that language is Java, you need UML for Java Programmers . In this book, one of the world's leading object design experts becomes your personal coach on UML 1&2 techniques and best practices for the Java environment. Robert C. Martin illuminates every UML 1&2 feature and concept directly relevant to writing better Java software--and ignores features irrelevant to Java developers. He explains what problems UML can and can't solve, how Java and UML map to each other, and exactly how and when to apply those mappings. Pragmatic coverage of UML as a working tool for Java developers Shows Java code alongside corresponding UML diagrams Covers every UML diagram relevant to Java programmers, including class, object, sequence, collaboration, and state diagrams Introduces dX, a lightweight, powerfully productive RUP and XP-derived process for successful software modeling Includes a detailed, start-to-finish case study: remote service client, server, sockets, and tests.